Case Report: Fatal Multiorgan Failure and Heterochronous Pneumonitis Following Pembrolizumab Treatment in a Patient With Large-Cell Neuroendocrine Carcinoma of Lung - Xie, Xiaohong; Wang, Fei; Qin, Yinyin; Lin, Xinqing; Xie, Zhanhong; Liu, Ming; Ouyang, Ming; Luo, Bihui; Gu, Yingying; Li, Shiyue; Gu, Dejian; Chen, Rongrong; et al. (Frontiers in Pharmacology, 2021)
Immune checkpoint inhibitors have radically changed the landscape of antitumor therapies in several malignancies. Despite the long-term efficacy, severe immune-related adverse events (irAEs) were not uncommon. However, fatal simultaneous multiorgan failure was rare. Here, we described a patient who developed multiorgan failure, including fulminant myocarditis, myasthenia gravis crisis, hepatic dysfunction, and delayed pneumonitis after pembrolizumab therapy for lung large-cell neuroendocrine carcinoma. After failure of high-dose steroid treatment, implantation of cardiac pacemaker combined with high-dose steroids successfully controlled myocarditis caused by immune checkpoint inhibitors (ICIs). Delayed pneumonitis occurred unexpectedly, and it was treated successfully with steroids. With wild adoption of ICIs in clinical practice, investigations for predictive markers of irAEs are warranted, and more successful treatment strategies are worth sharing.